Obscuring Sexual Crime: Examining Media Representations of Sexual Violence in Megan's Law - Shelby, Renee M (2013)
Sexual violence remains a pervasive and persistent social problem. In 1996, Congress enacted Megan’s Law, dictating mandatory community notification and potential civil commitment for those deemed by the State to be “dangerous sexual offenders.” In 2013, Megan’s law continues to influence the treatment of sexual offenders under law and the social construction of a highly publicized, yet statistically rare, sexual crime—the rape and murder of a young female child by a depraved male stranger. This influence highlights the extent to which this personalized crime bill shapes the social construction of sexual violence in terms of sex and gender systems. This project examines how sex and gender shape media discourses of the sexual offender and victim that are mobilized in the legislative debate on Megan’s Law. Drawing on theoretical ideas from cultural studies and feminist legal scholarship, I employ discourse analysis to analyze the legislative debate on Megan’s Law